Dramatic uneven urbanization of large cities throughout the world in recent decades - Sun, Liqun; Chen, Ji; Li, Qinglan; Huang, Dian (Nature communications, 2020)
The world has experienced dramatic urbanization in recent decades. However, we still lack information about the characteristics of urbanization in large cities throughout the world. After analyzing 841 large cities with built-up areas (BUAs) of over 100 km 2 from 2001 to 2018, here we found an uneven distribution of urbanization at different economic levels. On average, large cities in the low-income and lower-middle-income countries had the highest urban population growth, and BUA expansion in the upper-middle-income countries was more than three times that of the high-income countries. Globally, more than 10% of BUAs in 325 large cities showed significant greening ( P < 0.05) from 2001 to 2018. In particular, China accounted for 32% of greening BUAs in the 841 large cities, where about 108 million people lived. Our quantitative results provide information for future urban sustainable development, especially for rational urbanization of the developing world. Urban development has dramatically increased in recent decades. Analyzing 841 large cities throughout the world for the period from 2001 to 2018, the authors disclosed uneven features of global urbanization in terms of urban expansion, population growth, and greening at different economic levels.